Обет на крови: [роман] / Александр Тамоников - Тамоников Александр (Честь имею, 2006)
Экземпляры: АБ (20191217) / Инвентарный номер: 51135 / Цена: 88.20 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 17 / ББК: 84(2Рос=Рус)6